BUILDING PARTNERSHIP BETWEEN STATE AND NON-STATE ACTOR IN TOURISM VILLAGE OF YOGYAKARTA - Machya Astuti Dewi; Ariesani Hermawanto; Sri Issundari; Susanta Susanta (Prima Center Indonesia, 2016)
The rapid growth of tourism village in the province of Daerah Istimewa Yogyakarta (DIY) strengthens the important meaning of the existence of the non-state actors in international relations. Since growing in early 2000s and exceptionally developing nowadays, the community in tourism village has shown that the activities, attractions, art culture, and customs they has demonstrated to their foreign guests are able to serve as a means of accomplishing cultural diplomacy that feature the characteristic of people-to-people contact. However, their position and role as the non-state actors have not been autonomous. There are many obstacles in the development of tourism village that forces the state (the local government of DIY province) to help, attend, and facilitate the people in tourism villages. This The result is the collaborative and accommodating relation between the people and the local government, so that the tourism villages can grow fast in DIY province.Key Words: Tourism Village, Non State Actor, People-to-People Contact, Yogyakarta